Knowledge and attitudes toward COVID-19 vaccination among student nurses from Saudi Arabia - Romeo Mostoles Jr; Richard Maestrado; Joyce Buta; Salman Alsaqri; Evalynn Rondilla; Hamdan Mohammad albaqawi (Universitas Airlangga, 2022)
Introduction: Insights into the knowledge and attitudes of students can be achieved by analyzing their general understanding and prevention of the coronavirus. Therefore, it is imperative to identify attributes that influence the development of healthy behaviors among students. This study aimed to determine the dynamics of knowledge and attitudes of student nurses concerning the COVID-19 vaccine. Methods: This descriptive-cross sectional study involved 250 student nurses from the University of Hail, Nursing College, selected by convenience sampling. The data were collected between August and September 2021 using questionnaires. The data were analysed using a t-test, one-way ANOVA, and Pearson’s correlation test with a significance level of 0.05. Results: The study results showed that participants have good knowledge (mean = 3.09; SD = 0.88) and attitudes (mean = 8.62; SD = 1.83). Gender(except for knowledge), marital status, and age were not relevant as explanatory factors of knowledge and attitude. There was a significant difference in both knowledge (F = 2.233; p < 0.005) and attitude (F = 3.918; p < 0.004) associated with the course year. There was no significant relationship between knowledge and attitude (r = -0.013; p-value = 0.834). Conclusions: This information is critical for educators as they design techniques to help students put their knowledge into practice. In this way, educators may help health students develop skills and encourage students to become accountable health professionals who can support current societal healthcare demands.